Professional exams as an element of professionalization of administration - Lončar, Zoran (Zbornik radova Pravnog fakulteta u Novom Sadu, 2021)
In recent years, a significant reform has been implemented in Serbia in the field of professional development of civil servants, but professional exams have remained outside the essential reform processes. An extremely large number of professional exams, which today are conducted by various state and provincial administration bodies, are taken not only by state, provincial and local officials, but also by subjects outside the public administration system, require priority systematic regulation of a number of legal issues laying in the right way contributed to the process of professionalization of the administration. Given that the state professional exam appears as a general exam and that all employees are required to pass it, regardless of the type of administrative body in which they work, the central place in the reform of the system of professional exams in the administration should belong to this type of exam. Legal regulations should precisely regulate the relationship between the state professional exam and all other special or professional exams, primarily through the issue of exam programs, and then the manner of education and composition of examination commissions, exam fees, exam procedures, keeping records of passed exams, issuing certificates, etc. Legal regulations should precisely regulate the relationship between the state professional exam and all other special or professional exams, primarily through the issue of exam programs, and then the manner of education and composition of examination commissions, exam fees, exam procedures, keeping records of passed exams, issuing certificates, etc. Further successful continuation of the process of professionalization of the administration depends on the manner in which the mentioned issues will be regulated, because without a well-designed and carefully constructed system of professional exams, results achieved in previous years in the field of professional development of employees will remain without real significance.